Social Entrepreneurship and Microfinance in Kenya - TADELE, Haileslasie (Journal of Advanced Research in Law and Economics, 2020)
This research examines the determinants of entrepreneurial orientation of individuals and investigates the role of microfinance in improving social entrepreneurship. The study uses survey data on a sample of 200 respondents from Kenya. The paper investigates the determinants of entrepreneurial orientation using socio-economic factors and microfinance borrowing as independent variables and entrepreneurial orientation as dependent variable. This model is estimated using an ordinary least square (OLS) regression model. The paper finds that higher educational level, greater access to credit, access to business skill trainings and microfinance borrowings tend to improve entrepreneurial orientation of individuals. The findings also indicate that microfinance borrowers tend to have higher risk taking and pro-active behavior indicating a higher entrepreneurial orientation than non-borrowers. The study thus confirms the role of microfinance in improving entrepreneurial orientation of borrowers and emphasizes the socio-economic factors that significantly affect entrepreneurial orientation of individuals. The findings have implications for further research on the growth constraints that impact microfinance institutions in promoting social entrepreneurship.